THE PRACTICE OF 'NEMBAK SIM' AND ITS IMPACT ON DRIVING SAFETY AMONG STUDENTS IN SURABAYA - Muhammad Daffa Rizki Abidin; Agus Machfud Fauzi (Jurnal Analisa Sosiologi, 2025)
The phenomenon of "nembak SIM," which refers to obtaining a Driver's License (SIM) without going through the official examination process, has become an issue that poses a potential risk to road safety, especially among students. This study aims to analyze the impact of this practice on the road safety of students at the State University of Surabaya (UNESA) using a descriptive qualitative approach through in-depth interviews. The results indicate that students who obtained their SIM through illegal means have a lower understanding of traffic rules, are more likely to violate regulations, and are more prone to being involved in accidents. Theoretically, this research contributes to understanding the impact of administrative social deviance on road safety behavior, as well as highlighting the importance of comprehensive traffic awareness and education. Methodologically, this study offers a qualitative interview approach as an effective tool to explore individuals' perceptions and experiences regarding the "nembak SIM" practice, which can serve as a foundation for further research on social behavior in the context of traffic safety. The results showed that students who obtained their driver's license through illegal channels tend to have a lower understanding of traffic rules and break the rules more often than those who took the official exam. In addition, this group also had more accidents due to a lack of preparedness in dealing with situations on the road. In conclusion, the practice of “SIM shooting” contributes to the low driving safety of UNESA students. Therefore, there is a need for more intensive education on the importance of obtaining a driver's license officially as well as increased awareness of the risks of driving on the road without adequate skills.